Roles of Beta2- and Beta3-Adrenoceptor Polymorphisms in Hypertension and Metabolic Syndrome - Kazuko Masuo (International Journal of Hypertension)
Hypertension, diabetes mellitus (especially type 2 diabetes mellitus), metabolic syndrome and obesity are rapidly growing public health problems. Sympathetic nerve activation is observed in obesity, hypertension and diabetes mellitus, which have strong genetic as well as environmental determinants. Reduced energy expenditure and resting metabolic rate are predictive of weight gain, and the sympathetic nervous system participates in regulating energy balance through thermogenesis. The thermogenic effects of catecholamines in obesity have been mainly mediated via the 𝛽2- and 𝛽3-adrenergic receptors in humans. Further, 𝛽2-adrenoceptors importantly influence vascular reactivity and may regulate blood pressure. Genetic polymorphistns of the 𝛽-adrenoceptor gene have been shown to alter the function of several adrenoceptor subtypes and thus to modify the response to catecholamine. 𝛽2-adrenoceptor polymorphisms (Arg16Gly, Gln27Glu, and Thr164Ile) have been studied in relation to hypertension. Genetic variations in the 𝛽3-adrenoceptor (i.e. Try64Arg variant) are also associated with both obesity and hypertension. However, the precise relationships of the polymorphisms of 𝛽2- and 𝛽3-adrenoceptor genes with sympathetic nervous system activity, hypertension, and metabolic syndrome have not been fully clarified. This paper will discuss the current topics involving the influence of the sympathetic nervous system and 𝛽2- and 𝛽3- adrenoceptor polymorphisms in hypertension and metabolic syndrome.